Penerapan Solution Focused Brief Counseling Untuk Mengurangi Prokrastinasi Akademik Pada Siswa Sman 18 Surabaya: Implementation of Solution Focused Brief Counseling to Reduce Academic Procrastination in Students of Sman 18 Surabaya - Wahyudi, Moh. Wildan Wahyudi; Bakhrudin All Habsy; Nurudducha (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
Academic procrastination, namely the behavior of procrastinating or avoiding academic tasks, has a significant relationship with students in several ways, both from a cognitive, emotional and academic perspective. Procrastination can directly affect students' academic performance. When students procrastinate on assignments, they may end up having to complete the work in a very short time, which can result in low quality work, tardiness, or even failure to complete assignments. This can lead to a decrease in academic grades and a negative impact on overall academic performance. This study aims to evaluate the effectiveness of implementing Solution Focused Brief Counseling (SFBC) in reducing academic procrastination students in high school 18 Surabaya. This research uses the Classroom Action Research (PTK) method with two intervention cycles. In cycle 1, counseling focuses on identifying problems and using the miracle question technique to set goals. In cycle 2, researchers applied additional techniques such as exclusion questions and action planning to strengthen behavior change. The research sample consisted of 15 students selected through purposive sampling techniques, and data was collected through interviews and observation. The research results show that the implementation of SFBC is effective in reducing students' levels of academic procrastination. At the end of cycle 1, there was an increase in students' awareness of the impact of procrastination and achieving initial goals. Cycle 2 saw a more significant reduction in procrastination behavior, with students showing increased engagement and better time management. Data analysis shows that exception questioning and action planning techniques contribute to more consistent and sustainable behavior change